Sistem Keamanan Ruang Server Rumah Sakit Swasta Berbasis Mikrokontroler Arduino dan Android - Angelina Hadriani Hadriyanto; Agung Budi Susanto; Abu Khalid Rivai (LPPM STMIK AL MUSLIM, 2023)
The security of the server room is very important, considering that a lot of important data is stored in it, the server room door locking system which still uses conventional keys is very vulnerable to break-ins into the server room because conventional keys are very easy to duplicate, besides that the use of conventional keys is very risky of human error because It's human nature to forget to put keys all over the place. Besides that, maintenance work that is usually done by IT staff to check the condition of the server room is also hampered by having to go back and forth to security to borrow and return keys before and after carrying out routine maintenance activities. By utilizing the development of Android and Arduino smartphone technology in this study, the authors aim to make SK applications and SMS alarms to replace the current server room security system which is still manual using conventional keys. With this new system, the unlocking process can be through an application embedded in an Android smartphone. by pressing the buttons provided in the application. The research method used is the Prototype method. The way this security system works is that the user or users must open the application on Android and then connect it to the Bluetooth module. After the application and the Bluetooth module are connected, the user only has to choose whether to open or lock the door according to the options in the image in the application, and for the workings of the security system. sms alarm if the PIR sensor detects the movement of people in the server room then the PIR sensor will forward the command to GSM module to send sms to smartphone user.